Induction of defense responses against Magnaporthe oryzae in rice seedling by a new potential biocontrol agent Streptomyces JD211. (14th June 2018) - Shao, Zhengying; Li, Zhang; Fu, Yanhui; Wen, Yangping; Wei, Saijin
Abstract : The induced resistance against plant pathogens via biocontrol agents is considered as an eco‐friendly and promising strategy. In this study, the induced resistance against Magnaporthe oryzae ( M. oryzae ) in rice seedling by a new potential biocontrol agent Streptomyces JD211 (JD211) was evaluated. The effects of JD211 on defense‐related enzymes activities and defense genes expression were investigated. The biocontrol efficacy of different JD211 concentrations was different, and the treatment of 10 g kg −1 JD211 achieved the highest biocontrol efficacy. Activities of catalase, phenylalanine ammonia‐lyase (PAL) and β‐1, 3‐glucanase significantly increased in the presence of JD211. The gene expression level of both PAL and pathogenesis related protein 1 increased when rice seedlings were inoculated with JD211 alone or co‐inoculated with M. oryzae, and the expression level of chitinase gene was enhanced by JD211 in the later stage. All results suggested that JD211 could increase the rice resistance by stimulating a series of defense responses, which was the result of induced systemic resistance by JD211. This work will provide a new biocontrol agent against Magnaporthe oryzae in rice seedling.